2008
DOI: 10.1016/j.immuni.2008.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Selective CD4+ T Cell Help for Antibody Responses to a Large Viral Pathogen: Deterministic Linkage of Specificities

Abstract: Antibody responses are critical components of protective immune responses to many pathogens, but parameters determining which proteins are targeted remain unclear. Vaccination with individual MHC-II-restricted vaccinia virus (VACV, smallpox vaccine) epitopes revealed that CD4(+) T cell help to B cells was surprisingly nontransferable to other virion protein specificities. Many VACV CD4(+) T cell responses identified in an unbiased screen targeted antibody virion protein targets, consistent with deterministic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
170
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 168 publications
(188 citation statements)
references
References 50 publications
11
170
2
Order By: Relevance
“…According to this notion, specific B cells internalize and process the antigen, leading to the presentation of antigen fragments bound by surface MHC class II molecules that can be recognized by specific T cells guaranteeing that the T cells deliver help to B cells specific for the same antigen (linked help). Although in some instances it has been shown that T cells can only or preferentially provide help to B cells specific for the same protein (17,18), in other systems this restriction was not the case (19,20). It was found that two proteins that are present on the same particle could function together and that T cells specific for one protein could provide help for B cells specific for the second protein (20).…”
Section: Previously Undescribed Grass Pollen Antigens Are the Major Imentioning
confidence: 99%
“…According to this notion, specific B cells internalize and process the antigen, leading to the presentation of antigen fragments bound by surface MHC class II molecules that can be recognized by specific T cells guaranteeing that the T cells deliver help to B cells specific for the same antigen (linked help). Although in some instances it has been shown that T cells can only or preferentially provide help to B cells specific for the same protein (17,18), in other systems this restriction was not the case (19,20). It was found that two proteins that are present on the same particle could function together and that T cells specific for one protein could provide help for B cells specific for the second protein (20).…”
Section: Previously Undescribed Grass Pollen Antigens Are the Major Imentioning
confidence: 99%
“…5). CD4 ϩ T cell help is critical for induction of VACV-specific Abs, and depleting these cells abrogates IgM and IgG Ab responses to the virus (1,47,60). When either CD4 ϩ or CD8 ϩ T cells were depleted individually, vv-VCPko still formed smaller lesions and had reduced viral titers.…”
Section: Discussionmentioning
confidence: 99%
“…The Ab response to poxviruses is almost completely Th dependent (12,47,60). Therefore, depleting CD4 ϩ T cells also eliminates Ab responses (12,47,60). To address the contributions of enhanced nAb and CD8 ϩ T cell responses during infection with vv-VCPko, we depleted mice of CD8 ϩ and CD4 ϩ T cells individually or together and examined lesion sizes (Fig.…”
Section: Cd8 ؉ T Cells and Cd4 ؉ T Cells Contribute To Attenuation Ofmentioning
confidence: 99%
“…This potential dichotomy between intact Pns and conjugate may reflect a requirement for covalent attachment of PPS14 to immunogenic protein, as is present in conjugate but not Pns, to elicit PPS14-specific IgG memory. In this regard, it was recently demonstrated that, in response to intact vaccinia virus, CD4 ϩ T cell help for an in vivo IgG response to a specific viral protein was mediated strictly by CD4 ϩ T cells with the same protein specificity as the B cell, despite there being a number of distinct immunogenic proteins expressed by the intact virion (34). This dependence on intramolecular help suggests the possibility that B cell samples isolated or covalently linked Ags following dendritic cell and/or macrophage transport, processing and/or membrane expression of intact pathogen.…”
Section: Discussionmentioning
confidence: 99%